KEPUASAN PENGUNJUNG DALAM RANGKA PENGEMBANGAN OBJEK WISATA DI KABUPATEN KEDIRI TAHUN 2016 - Widyatmoko, Sardjono, Setyawan, Sigit, Sardjono, Moch Haris (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2016)
ABSTRACTImproved service and repair facility must be done so that visitors do not get bored for a return visit, because if the services and facilities of a tourist attraction well then the visitors will come back to visit these attractions. Tourism Object potential to attract visitors in Kediri very much. Sightseeing in Kediri district were: Tegowangi Temple, Temple Surowono, Simpang Lima Gumul, Kelud, Ubalan, Niagara Irenggolo, Petilasan Sri Aji Joyoboyo, and The Old Church Puhsarang. This method is a method that can be used to understand the object that becomes the problem. Judging from the existing problems and objectives, this study classified as survey research is "research that takes a sample of the population and the use of a questionnaire as a main data retrieval tool" Singarimbun and Effendi (1999: 40) The survey was conducted by direct field observations are accompanied by interviews with local people, community leaders and government officials who are competent to tourism in the context of collecting data and information. For that use a checklist and implemented at all locations assessed as a potential object locations. In a visit to the sites in question, also conducted Deep discusion groups / in-depth discussion involving the community, leaders and the competent government authorities. Data and information were analyzed with SWOT method, which takes into consideration a variety of factors that contribute to negative or positive: strengths, weaknesses, opportunities and threats of the tourist attraction. Through the process will be done conclusion that the results of the survey point, which is then followed by the development of the recommendations, increased tourism facility in Kediri Key Words: Tourism, Statisfaction, Objek, Kediri District